Legal Review of the Effect of OJK Regulation Number 11/POJK.03/2016 on the Implementation of Sharia Banking Business Activities on the Sustainability of the Sharia Financial Industry in Indonesia - Jahir, Siska Sanjahaya; Surahmi, Mila; Nasution, Emmi Rahmiwita (West Science Law and Human Rights, 2025)
This study analyzes the impact of OJK Regulation Number 11/POJK.03/2016 on the implementation of sharia banking business activities and its role in ensuring the sustainability of the sharia financial industry in Indonesia. The regulation aims to strengthen governance, risk management, and transparency in sharia banking while promoting alignment with Islamic principles. Employing a qualitative juridical analysis, this research evaluates the regulation's effectiveness and identifies challenges faced by sharia banking institutions, including resource limitations, knowledge gaps, and regulatory ambiguities. The findings reveal that while the regulation has significantly improved compliance, risk management, and public trust, challenges persist in its practical implementation. Recommendations include capacity building, regulatory clarity, and technological adoption to optimize the regulation's impact. This study contributes to the understanding of regulatory frameworks in Islamic finance and offers insights for enhancing the resilience and sustainability of Indonesia's sharia financial industry.